2005
DOI: 10.1111/j.1346-8138.2005.tb00793.x
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal Lupus Erythematosus: A Review of the Racial Differences and Similarities in Clinical, Serological and Immunogenetic Features of Japanese versus Caucasian Patients

Abstract: There has been tremendous interest in neonatal lupus erythematosus (NLE) since the reports of anti-Ro/SSA antibodies as a diagnostic marker. Recent studies, including ours, have revealed racial differences as well as similarities in the clinical features and immunogenetic backgrounds of Japanese and Caucasian patients with NLE. The frequency of photosensitivity and subacute cutaneous LE lesions is not high in Japanese infants with NLE, which is in sharp contrast to their Caucasian American counterparts. The ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 70 publications
0
7
0
Order By: Relevance
“…In a study of 193 NLE cases in Japan and a study of 17 NLE cases in Thailand, skin lesions were found in 85.5% and 70.6% of neonates, respectively . Thus, cutaneous manifestation appears to be extremely common in China, even compared to other Asian countries, suggesting that there might be ethnic or geographic differences with the symptoms of NLE, although currently only a few studies have explored this possibility . Furukawa et al .…”
Section: Discussionmentioning
confidence: 99%
“…In a study of 193 NLE cases in Japan and a study of 17 NLE cases in Thailand, skin lesions were found in 85.5% and 70.6% of neonates, respectively . Thus, cutaneous manifestation appears to be extremely common in China, even compared to other Asian countries, suggesting that there might be ethnic or geographic differences with the symptoms of NLE, although currently only a few studies have explored this possibility . Furukawa et al .…”
Section: Discussionmentioning
confidence: 99%
“…The presence of certain major histocompatibility complexes such as human leukocyte antigen B8 and human leukocyte antigen DR3 in the mother predisposes the infant to NLE and congenital heart block [17, 18]. Although there is no apparent racial predilection, disparity in outcomes between minorities and whites has been observed [5, 10, 16, 1820]. Like many autoimmune diseases, reports from the Research Registry for Neonatal Lupus/US indicate that the female-to-male ratio is approximately 2 : 1 with cutaneous NLE, but the gender distribution for cardiac disease is approximately equal [21, 22].…”
Section: Epidemiologymentioning
confidence: 99%
“…Anti‐Ro/SSA antibodies in Japanese mothers were also found to cause neonatal lupus syndrome. Congenital heart block was found in 50% of these complicated newborns, similar in frequency to Caucasians 26 …”
Section: Association Of Autoantibodies With Clinical Featuresmentioning
confidence: 57%